PSYCHOLOGICAL FIRST AID (PFA) PADA KORBAN DI UPTD PPA KOTA MAKASSAR - Murdiana, Sitti; Arifin, Putri Amaliah; Muhammad, Essam S.Sappe Abdulwahid; Patonangi, Andi Iftitah Mutiara; Israk, Israk (LPPM Institut Pendidikan Nusantara Global, 2023)
The Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) in Makassar City is a service that fully re-empowers women and children who are victims of violence. One of the interventions that can be carried out in handling the client's psychological condition at the beginning of dealing with the problem of acts of violence experienced is by applying Psychological First Aid (PFA). The Psychological First Aid (PFA) model provided is the Johns Hopkins RAPID PFA model. There are five phases in the RAPID PFA model, namely: Rapport, Assessment, Priority, Intervention, and Disposition. The SDQ-25 and DASS-21 scales were also given to see the range of the victim's psychological condition after administration of PFA. The victims who were given PFA were 3 people with the initials D, F and NR. Based on the results of the implementation of the PFA, it can be seen that the psychological state of the victim is generally in the normal category. So, it can be concluded that the application of PFA is proven to be able to make victims feel calmer, safer and connected.